2010
DOI: 10.2214/ajr.09.3174
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of MR Enterography Versus Capsule Endoscopy for the Surveillance of Adult Patients With Peutz-Jeghers Syndrome

Abstract: MR enterography is a promising alternative to capsule endoscopy for small-bowel surveillance in adults with PJS. Although our results suggest that capsule endoscopy is more comfortable for the patient, MR enterography may be less prone to missing large polyps and may be more reliable in their size assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 29 publications
1
91
1
2
Order By: Relevance
“…In specialized centers, CE is used to identify large polyps and to apply BE to remove them. 27,28 The effect on the incidence of intussusceptions remains to be established in prospective trials, though. 29 Adenoma or adenocarcinoma were observed in 9 of 30 polyps (30.0%) > 20 mm and in 1 of 80 polyps (1.3%) ≤20 mm and were resected endoscopically.…”
Section: Endoscopic Resection Of Small Intestinal Polyps Stricture Dmentioning
confidence: 99%
“…In specialized centers, CE is used to identify large polyps and to apply BE to remove them. 27,28 The effect on the incidence of intussusceptions remains to be established in prospective trials, though. 29 Adenoma or adenocarcinoma were observed in 9 of 30 polyps (30.0%) > 20 mm and in 1 of 80 polyps (1.3%) ≤20 mm and were resected endoscopically.…”
Section: Endoscopic Resection Of Small Intestinal Polyps Stricture Dmentioning
confidence: 99%
“…It has been shown that, for polyps measuring more than 10 mm in diameter, MRE has equal sensitivity to video capsule endoscopy (VCE). (8) Even though detection of small polyps is better with VCE, it cannot be used in the presence of obstruction. (9,10) On radiography, intussusception may be seen as a soft tissue mass, commonly occupying the right upper quadrant.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the high risks associated with clinically significant SB polyps (C1.5 cm), current guidelines recommend that patients with PJS aged C8-10 years, should undergo SB surveillance using a minimally invasive modality such as SB capsule endoscopy (SBCE) and/or radiological diagnostic imaging [magnetic resonance enterography/enteroclysis (MRE)] on a biennial to triennial basis [211,220,221] in order to facilitate early detection of large PJS polyps and also to investigate for possible occult SB malignancies. SBCE is very well tolerated by patients and is a less invasive option for the surveillance of the SB in patients with PJS [220].…”
Section: Peutz-jeghers Syndromementioning
confidence: 99%
“…SBCE is very well tolerated by patients and is a less invasive option for the surveillance of the SB in patients with PJS [220]. The limitations relating to SBCE include its potential to miss clinically significant polyps, especially if these are located within the proximal SB [220,221,[226][227][228] and challenges relating to the estimation of polyp size and location and (Fig.…”
Section: Peutz-jeghers Syndromementioning
confidence: 99%